Incidence and Intensity of Disease Attack on Snake Plants (Sanseviera trifasciata) in Palembang City - Hamidson, Harman; Farras, M. Irsal; Safitri, Ayu; Pratama, Rahmat (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2025)
Ornamental plants are important horticultural commodities with considerable economic value, providing income for both growers and traders. Among them, Sansevieria trifasciata (commonly known as snake plant) is favored for its sword-shaped, rigid leaves. This study aimed to assess the incidence and intensity of disease in snake plants. The research was conducted from January to February 2025 using purposive sampling. Field observations revealed that the plants were affected by Colletotrichum sansevieria, causing necrotic black lesions. Disease incidence and intensity varied across locations, with the highest incidence (100%) observed in plants owned by Suwaji, Salikun, and Asep, and the lowest (10%) in those owned by Tina Purba and Sarkun. Disease intensity was greatest at Suwaji’s site (83.3%) and lowest at Tina Purba’s and Sarkun’s (3.3%). These differences were influenced by environmental factors such as temperature and humidity. Integrated disease management through physical, chemical, and biological methods is suggested as a strategy to suppress pathogen growth.